The Impact Of Work Environment And Compensation Toward Employee Performance - Sri Aprianti Tarigan; Aifin Assaly; ARIFIN; EDDY GUNAWAN; EDWARD HARNJO (Institute of Computer Science (IOCS), 2022)
From this research, it can be known that the employee performance at Union Education Center Medan can be explained by work environment in 50.9% and the remaining of 49.1% can be explained by other factors. Compensation in 54.6% and the remaining of 45.4% can be explained by other factors. The regression equation is Y=10.920+0.136X1+0.028X2, which means the increase of 1 unit of work environment will lead to increase of 0.136 units of employee performance at Union Education Center and the increase of 1 unit of compensation will lead to increase of 0.028 units of employee performance at Union Education Center. It also can be seen that work environment and compensation has impact toward employee performance. Because it is 6.322 > 3.26 (Fcount > +Ftable) this is why that the hypothesis alternative (Ha) is accepted while null hypothesis (Ho) is rejected. The study recommended that the company can provide a comfort workplace, more adequate equipment to support the teacher daily works. The company also need to pay attention to employee compensation to improve employee commitment and performance.